(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
WHO in its program, namely the Global School Health Initiative seeks to mobilize and strengthen health promotion and education activities in young children. One of the health education programs that could be held in elementary schools is the training of young pharmacists. Little Pharmacist, commonly abbreviated as Apocil, is an idea to introduce the role of the pharmacist profession more clearly from an early age. It is hoped that the presence of this little pharmacist in the future will increase elementary school students’ awareness of medication and introduce the pharmacist profession to students and the community. Student and community knowledge regarding health and medicine is still limited. Medications have an important role in maintaining health, therefore it should be used correctly in order to provide optimal clinical benefits. The purpose of this community service is to train little pharmacists in an effort to use the right medicine and educate healthy, nutritious food for elementary school students in Kemanisan Village. The method used was the Active Individual Learning Method (CBIA), the practice of making powder medicine, and it was evaluated by carrying out DAGUSIBU (get, use, store, and dispose of) mini-games. The media used in this activity are banners, mortar and stamper, and parchment paper. From the results of the activities was found that the students had known the pharmacist role and understood DAGUSIBU as well as education on healthy nutritious food with good results using mini-games. In summary, it can be concluded that the provision of education can increase the knowledge of elementary school students in the village of Kemanisan.